DNA repair - Donev, Rossen (Advances in protein chemistry and structural biology ;, 2019)
'DNA Repair, ' Volume 115 in the Advances in Protein Chemistry and Structural Biology series, provides an overview of current developments in mechanisms underlying DNA repair, their involvement in maintaining chromatin repair, the balance between chromosome breaks repair pathways, tumorigenesis, immune signaling and infection-induced inflammation. Specific chapters cover the Structure and function of the multi-subunit TFIIH with insights into nucleotide excision repair, Chromatin repair: how DNA packaging controls double-strand break repair, Controlling the balance between chromosome breaks repair pathways, The targeting of DNA repair pathways in the era of precision oncology, and much more. Key Features: Describes advances in our understanding on DNA repair mechanisms and the involvement of their dysregulation in promoting diseases; Presents data that is targeted to a very wide audience of specialists, researchers and students; Contains timely chapters written by well-renowned authorities in their field; Provides targeted information that is well supported by a number of high-quality illustrations, figures and tables. Readership: Protein chemists, biochemists, molecular biologists, cell biologists, immunologists, neuroscientists, structural biologists, medical doctors, pharmacologists, computational biochemists and other researchers working in this field. Articles published here would also be of a great benefit to medical, biology and pharmacology students specializing in this field. --